Pelatihan Strategi Pengembangan Sumber Daya Manusia Pada Para Hamba Tuhan (Pendeta) - Adriana Madya Marampa; Kres Ari Kawalo Barangan (Jurnal Nusantara Berbakti, 2023)
Human resource development strategy is the most absolute thing to do in an organization. This service was carried out on 40 prospective servants of God (Pdt). Several things that can be used to improve HR strategy, one of which is increasing leadership and commitment in service. The results of this service show that prospective servants of God can apply HR development strategies in order to improve their service.